Physiological and performance effects of dietary nitrate and N-acetylcysteine supplementation during prolonged heavy-intensity cycling - Tan, R.; Black, M.; Home, J.; Blackwell, J.; Clark, I.; Wylie, L.; Vanhatalo, A.; Jones, A. M. (Journal of Sports Sciences, 2022)
The purpose of this study was to investigate effects of concurrent and independent administration of dietary nitrate (NO3-), administered as NO3--rich beetroot juice (BR; ~12.4 mmol of NO3-), and N-acetylcysteine (NAC; 70 mg·kg-1) on physiological responses during prolonged exercise and subsequent high-intensity exercise tolerance. Sixteen recreationally active males supplemented with NO3--depleted beetroot juice (PL) or BR for 6 days and ingested an acute dose of NAC or maltodextrin (MAL) 1 h prior to performing 1 h of heavy-intensity cycling exercise immediately followed by a severe-intensity time-to-exhaustion (TTE) test in four conditions: 1) PL+MAL, 2) PL+NAC, 3) BR+MAL and 4) BR+NAC. Pre-exercise plasma [NO3-] and nitrite ([NO2-]) were elevated following BR+NAC and BR+MAL (both P < 0.01) compared with PL+NAC and PL+MAL; plasma [cysteine] was increased in PL+NAC and BR+NAC (both P < 0.01) compared to PL+MAL. Muscle excitability declined over time during the prolonged cycling bout in all conditions but was better preserved in PL+NAC compared to BR+NAC (P < 0.01) and PL+MAL (P < 0.05). There was no effect of supplementation on subsequent TTE . These findings indicate that co-ingestion of BR and NAC does not appreciably alter physiological responses during prolonged heavy-intensity cycling or enhance subsequent exercise tolerance.